Suicide in Siberian Aboriginal Groups - Lester, David (Archives of suicide research, 2006)
A search of historical documents about suicide in Siberian tribes in the 18th and 19th centuries indicated that they had very high suicide rates. It would be of great interest to explore suicidal behavior in these tribes today